Investigações in silico e proposição de farmacóforo na pesquisa de novos agentes tuberculostáticos - Viana, Jéssika de Oliveira (2019)
Tuberculosis, caused by Mycobacterium tuberculosis, is the infectious disease caused by bacteria with the highest levels of mortality worldwide, with numerous cases of resistance to first- and second-line drugs. Among the methods used in the search for new drugs are the insilico studies that perform the elaboration of chemical and biological models using computational tools in order to interpret molecular characteristics. In this perspective, the aim was to use QSAR (Quantitative Structure-Activity Relationships) and molecular modeling in order to propose a possible pharmacophore of benzothiazinone derivatives, which brings together structural characteristics responsible for the activity against M. tuberculosis. In this study, a set of 69 benzothiazinone derivatives was used, using computational tools such as: analysis of molecular descriptors with the aid of chemometrics, analysis of their quantum properties by means of electronic surfaces, prediction of metabolites, interactions with cytochrome P450 and molecular coupling in 4 proteins important for the bacillus: DprE1, InhA, PS and DHFR. As a result, the chemometric model computed in the Volsurf + and Pentacle programs presented good predictive values, where the descriptors referring to amphiphilicity and molecular volume were essential for biological activity. The electronic surfaces demonstrated the divergent character of the most active compounds of the study, corroborating with the QSAR studies. Metabolites from the interaction with CYP3A4 and CYP2D6 showed differences of coupling in the cytochrome isoforms, which may be due to the reaction medium and the existing divergences in the structure of the benzothiazinones, noting that their metabolites did not present changes in the structure of the pharmacophore proposed in the QSAR. Similarly, the molecular docking performed with the four TB enzymes showed good interactions of the most active compounds, where the fragments found in QSAR as essential for biological activity were also presented as essential for the interaction of the ligand with the active site of the proteins. Among the compounds of the series of benzothiazinones derivatives, compound 55 (11026134) presented the best profile for all analyzes of the study, noting that trifluoromethyl groups (position R1), nitro group (R2 position) and the piperazine moiety with hydrocarbon groups (position R3) are the likely pharmacophores for the benzothiazinones in the study.